Improving Prehospital Stroke Services in Rural and Underserved Settings With Mobile Stroke Units - Mathur, Shrey; Walter, Silke; Grunwald, Iris Q.; Helwig, Stefan A.; Lesmeister, Martin; Fassbender, Klaus (Frontiers in Neurology, 2019)
In acute stroke management, time is brain as narrow therapeutic windows for both intravenous thrombolysis and mechanical thrombectomy depend on expedient and specialised treatment. In rural settings, patients are often far from specialised treatment centres. Concurrently, financial constraints, cutting of services and understaffing of specialists for many rural hospitals have resulted in many patients being underserved. Mobile Stroke Units (MSU) provide a valuable prehospital resource to rural and remote settings where patient may not have easy access to in-hospital stroke care. In addition to standard ambulance equipment, the MSU is equipped with the necessary tools for diagnosis and treatment of acute stroke or similar emergencies at the emergency site. The MSU strategy has proven to be effective at facilitating time-saving stroke triage decisions. The additional on-board imaging helps to determine whether a patient should be taken to a primary stroke centre (PSC) for standard treatment or to a comprehensive stroke centre (CSC) for advanced stroke treatment (such as intra-arterial therapy) instead. Diagnosis at the emergency site may prevent additional in-hospital delays in workup, handover and secondary (inter-hospital) transport. MSUs may be adapted to local needs – especially in rural and remote settings – with adjustments in staffing, ambulance configuration and transport models. Further, with advanced imaging and further diagnostic capabilities, MSUs provide a valuable platform for telemedicine (teleradiology and telestroke) in these underserved areas. As MSU programmes continue to be implemented across the world, optimal and adaptable configurations could be explored.